Pengaruh Knowledge Management dan Job Experience terhadap Produktivitas Karyawan dengan Motivasi sebagai Variable Intervening: - Mochammad Iqbal Haras; Kusuma Chandra Kirana; E. Didik Subiyanto (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This research is intended to provide knowledge about the influence of knowledge management, job experience, and motivation on employee productivity. The aim is to find out how influential Knowledge Management, Job Experience, and Motivation on Employee Productivity are in the company. Employees of PT. Puninar JAYA will be the object of this research. This study used a questionnaire for data collection methods, using a sample of 75 respondents. The researcher uses quantitative research for this research, the methods that will be used are reliability tests and validity tests to test the quality of the data, and the data analysis techniques that will be used are classical assumption testing, multiple linear regression testing, and Sobel testing. Then the results of the research that has been done that Knowledge Management has a significant influence on employee productivity, job experience has a significant influence on employee productivity, motivation has a significant influence on employee productivity, knowledge management has a significant influence on motivation, job experience has a significant influence significant on motivation. Keywords: Knowledge management, Job experience, Employee productivity,